Devenir enseignant-chercheur à l'heure de l'autonomie des universités. Une recherche sur les représentations du métier chez les doctorants - Charlyne Millet; Emmanuelle Annoot (Université de Provence, 2017)
This article proposes a discussion on transformations that outline French higher education system in recent years, through the specific case of PhD students discovering the academic profession. We focus on the representations of these doctoral students with teaching missions from data collected by a questionnaire distributed to 41 PhD students in the human and social sciences, law and economic management, health sciences, literature and languages. Precisely, we analyze the link between two fundamental components of the profession: teaching and research. At the time of university autonomy, our results put forward a tendency for these beginners to the reproduction of the practices and the adhesion to the professional culture of their elders. These first conclusions enjoin us to an interrogation on the current professional identity of French academics and to pursue research on entry into a profession that is transformed, by federating research on the field.